Acidic Water Oxidation on Quantum Dots of IrOx/Graphdiyne. Issue 32 (19th June 2021) - Wang, Zhongqiang; Zheng, Zhiqiang; Xue, Yurui; He, Feng; Li, Yuliang
Abstract: Efficient acidic water oxidation utilization in the oxygen evolution reaction (OER) is still an important bottleneck for hydrogen production. From fundamental principles, a controllable graphdiyne (GDY) induced growth strategy is established; highly uniform size distribution of oxidized iridium quantum dots is prepared on the surface of graphdiyne (IrOx QD/GDY). The result shows that, the catalyst exhibits excellent activity and durability for acidic OER, with a current density of 10 mA cm −2 at a small overpotential of 236 mV versus the reversible hydrogen electrode (RHE) and a Tafel slope of 70 mV dec −1 . The performance is greatly superior to previously reported electrocatalysts. Remarkably, the acidic electrolyzer using IrOx QD/GDY as both cathode and anode electrodes can reach 10 mA cm −2 only at a much low cell voltage of 1.49 V (vs RHE). The results show the superior advantages of graphdiyne in effectively increasing numbers of the catalytically active sites for improving the charge transfer behavior and protecting the metal catalysts from corrosion. Abstract : The controllable growth of highly uniform and dispersed iridium oxide quantum dots is achieved via a graphdiyne (GDY) special structure. This catalyst shows the best catalytic performance in terms of the activity and durability for acidic oxygen evolution reaction. Remarkably, the IrOx QD/GDY based acidic electrolyzer only needs a cell voltage of 1.49 V to reach 10 mA cm −2 .